Principles of estimating - Holroyd, Trevor M. (Thomas Telford, 2000)
Current practice on most contracts dictates that the engineer deals with engineering matters and the quantity surveyor covers the commercial aspects. This book provides engineers with a sound all-round ability and commercial adeptness in price estimating.